Bank Guarantees in the Czech Republic - Liška, Petr (Archives of Business Research, 2023)
The article is focused on the legal regulation of bank guarantees in the Czech Republic. Bank guarantees have a significant benefit for conducting foreign trade. Although the legal regulation in the Civil Code is relatively new, it follows on from earlier laws and international business practices. The article points out some specifics of Czech legal regulation and important court case law.